IMPLEMENTASI ALGORITMA NEGASCOUT PADA PERMAINAN NINE MEN’S MORRIS - Dany Kurniawan; Rosa Delima; Nugroho Agus Haryono (Jurnal Informatika, 2015)
Application development nowadays many are using technology/knowledge of Artificial Intelligence study. This research tries to make an intelligence agent that can play Nine Men’s Morris game using Negascout algorithm. The purpose of this research are to compare the effectiveness of Negascout algorithm in exploring the best move along with time that required, compared with Alpha-Beta Pruning algorithm.  The result from this research are Negascout algorithm explores fewer nodes and require less time in the search of the best move compared with Alpha-Beta Pruning algorithm.